The relationship between playing and the motor and communicable aspects of children with cerebral paralysis - da Silva, Fabiola Antunes; dos Santos, Camila Boarini; Sant' Anna, Maria Mandalena Moraes; Rocha, Aila Narene Dahwache Criado (Faculdade de Filosofia e Ciências, 2021)
Cerebral Palsy (PC) can cause difficulty in playing actions due to restricted opportunities, routine therapies, architectural barriers, inexperience in playing with peers, difficulty in cognitive development and difficulty expressing their emotions. The aim of this study was to identify the relationship between playing the gross, manual and communicative motor skills of children with CP. Seven children with a diagnosis of PC with an average age of 4 years and their respective caregivers participated in the study. In order to collect data, the model was used to evaluate the Gross Motor Function Measurement Classification System (GMFCS), Manual Ability Classification System (MACS), Mini-Manual Ability Classification System for children with cerebral palsy (Mini-MACS) of Communication Function Classification (CFCS). To analyze the results, we used the IBM SPSS Statistics, version 22 software to perform the statistical analysis of the study, using the Pearson Correlation Coefficient. The results of this study showed that the higher the level of motor impairment, the lower was the score presented in the ACL, demonstrating that there is impairment in playing. It is concluded that the Playful Model is an evaluation that allows the child to build the profile of the child's abilities, interests and personal characteristics, allowing the professional to draw up the treatment plan according to the real needs of the child and those responsible. It is suggested that further studies be carried out in order to increase the number of participants, as well as propose an intervention program, focused on the difficulties identified in the standardized evaluations.